Redes de ciudadanía ante la deficiencia estatal: el caso de una organización social en San Juan de Lurigancho, Lima - Alarcón Delgado, David (2023)
The research analyzes how social organizations influence the construction of citizenship networks in urban spaces with state deficiency. Based on the analysis of the networks of citizenship in the case study —the social organization “La Lombriz Feliz” in the district of San Juan de Lurigancho (Lima)— it is intended to show that the organization contributes to the formation of citizenship by developing activities that supplement the deficiencies of the local State.